Equality Of Parenting Accepted By Parent Of Preschool Children Invillage Sridadi Rembang - Vicky Riyan Pranata; Estetika Putri; Indanah Indanah; Sri Karyati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Background: In the 80's, parents in educating their children, must experience differencesin today's digital era. Parenting patterns of parents who initially experienced differencesfrom other parents, who only applied authoritarian, permissive, and democratic parentingstyles have experienced success in educating children, but in the digital era, these threeparenting styles will not succeed, if they do not do synchronization according to the timeof the situation and conditions in terms of parenting.Objective: To find out the similarity of parenting received by parents in preschool childrenin Sridadi Village, Rembang in 2021.Methods: This study uses quantitative research methods with correlation research. Crosssectional approach method. The sample collection technique used is the ProportionateStratified Random Sampling method, the population in the village is 163 and the sampleis 116 respondents. Bivariate analysis using Spearman Rho test and the instrument usedis a questionnaire sheet.Results: The results showed that out of 116 respondents who had fairly good parentingstyles, 93 respondents (80.2%) and 23 respondents (19.8%) had poor parenting styles.Conclusion: The similarity of parenting received by parents from 116 respondents topreschool age children mostly do good parenting with a frequency of 93 respondents(80.2%).